2006
DOI: 10.1002/jso.20596
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal lavage with distilled water during liver resection in patients with spontaneously ruptured hepatocellular carcinomas

Abstract: Spontaneously rupture of hepatocellular carcinoma is a life threatening and worse prognosis. Not only the lower rate of resection and hemodynamic unstable, but also the hepatic failure and recurrence. Distilled water irrigation had been applied in several cancer surgeries including colon, stomach, breast, ovary, and bladder; thus had good results in lowering the tumor spreading. We applied distilled water peritoneal lavage after liver resection in patients with spontaneous rupture of hepatocellular carcinoma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 9 publications
0
28
1
Order By: Relevance
“…Therefore, it is suggested that surgical manipulation only occasionally exfoliates and spreads cancer cells in the surgical field. Some previous studies have indicated cytocidal effects of hypotonic shock on cancer cells (15)(16)(17). A previous report demonstrated the cytocidal activity of distilled water on colorectal cancer cell lines in culture, and also discussed the optimal method of peritoneal lavage with distilled water during colorectal cancer surgery (15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that surgical manipulation only occasionally exfoliates and spreads cancer cells in the surgical field. Some previous studies have indicated cytocidal effects of hypotonic shock on cancer cells (15)(16)(17). A previous report demonstrated the cytocidal activity of distilled water on colorectal cancer cell lines in culture, and also discussed the optimal method of peritoneal lavage with distilled water during colorectal cancer surgery (15).…”
Section: Discussionmentioning
confidence: 99%
“…After the first report of Price in 1905, water for injection has been widely used for the irrigation of peritoneal cavity in order to destroy released cancer cells after surgery for several types of cancers including colorectal, gastric and hepatocellurar cancer as well as for bladder irrigation after transurethral resection of bladder tumours (Price 1905;Moskovitz et al, 1987;Chen et al, 2001;Brundell et al, 2002;Huguet et al, 2004;Lin et al, 2006;Chang et al, 2013). Water for injection has been shown to destroy bladder cancer cells in vitro through osmotic lysis (cytolysis) while some studies suggest that it may be more effective than BCG (Bolkier et al, 1991;Nargund et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For resectable ruptured HCC patients, emergency liver resection can achieve good early and long-term results [17] . It has been reported that long-term results of emergency hepatectomy are similar to those receiving elective surgery [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 98%
“…Peritoneal cavity lavage can clear the cancer cells that have already dispersed into the peritoneal cavity at the time of rupture. Lin et al [16] reported that distilled water peritoneal lavage resulted in significantly better survival time in patients with spontaneous rupture of HCC. For unresectable tumors, some local ablation methods are also effective in killing cancer cells, such as microwave coagulation, argon beam coagulation or injection of absolute alcohol.…”
Section: Discussionmentioning
confidence: 98%